Simplify: $\displaystyle exp(x^3 )^3 = exp(3x^3 )$ Is the answer right? Thanks.
Follow Math Help Forum on Facebook and Google+
No, not quite right. If you put some values in for x then you'll see that's it not right. The rule you need is: $\displaystyle (x^n)^m=x^{nm}$ Hope that helps!
Turns out the answer was infact: $\displaystyle exp(3x^3 ) $
Hello, Originally Posted by r_maths Turns out the answer was infact: $\displaystyle exp(3x^3 ) $ that was the answer you would have found if you followed the hint and that you found =) $\displaystyle \exp(x^3)^3=\left(e^{x^3} \right)^3=e^{3x^3}=\exp(3x^3)$
View Tag Cloud